The Decade of Action for Road Safety 2011-2020 : Lessons from Argentina - Raffo, Veronica; Bliss, Tony (World Bank, Washington, DC, 2014)
The United Nations decade of action for road safety 2011-2020 sets an ambitious goal to stabilize and then reduce by half the predicted level of traffic fatalities in low and middle-income countries by 2020. This goal should save around 5 million lives, avoid 50 million serious injuries, and provide an economic benefit of more than US$3 trillion. Impacts on this scale will enhance country and regional development opportunities. In line with this goal, the Global Plan for the Decade of Action for Road Safety 2011-2020 identified five priorities: 1) road safety management capacity, 2) infrastructure safety, 3) vehicle safety, 4) road user behavior, and 5) post-crash care. This integrated development perspective is also reflected in the World Bank's new transport sector business strategy. The project's inclusive approach delivers road safety interventions in the demonstration corridors and elsewhere.